Critical Role of macrophage FcγR signaling and ROS in alloantibody-mediated hepatocyte rejection - Zimmerer, Jason M. (J Immunol, 2018)
Humoral alloimmunity negatively impacts both short- and long-term cell and solid organ transplant survival. We previously reported that alloantibody-mediated rejection (AMR) of transplanted hepatocytes is critically dependent on host macrophages. However, the effector mechanism(s) of macrophage-mediated injury to allogeneic liver parenchymal cells is not known. We hypothesized that macrophage-mediated destruction of allogeneic hepatocytes occurs by cell-cell interactions requiring Fcγ receptors (FcγRs). To examine this, alloantibody-dependent hepatocyte rejection in CD8-depleted wild-type and Fcγ chain KO (lacking all functional Fcγ receptors) transplant recipients was evaluated. Alloantibody-mediated hepatocellular allograft rejection was abrogated in recipients lacking FcγR compared to wild-type recipients. We also investigated anti-FcγRI mAb, anti-FcγRIII mAb, and inhibitors of intracellular signaling [to block phagocytosis, cytokines, and reactive oxygen species (ROS)] in an in vitro alloantibody-dependent, macrophage-mediated hepatocytoxicity assay. Results showed that in vitro alloantibody-dependent, macrophage-mediated hepatocytotoxicity was critically dependent on FcγRs and ROS. The adoptive transfer of wild-type macrophages into CD8-depleted FcγR-deficient recipients was sufficient to induce AMR, while adoptive transfer of macrophages from Fcγ chain KO mice or ROS-deficient (p47 KO) macrophages was not. These results provide first evidence that alloantibody-dependent hepatocellular allograft rejection is mediated by host macrophages through FcγR signaling and ROS cytotoxic effector mechanisms. These results support the investigation of novel immunotherapeutic strategies targeting macrophages, FcγRs and/or downstream molecules, including ROS, to inhibit humoral immune damage of transplanted hepatocytes and perhaps other cell and solid organ transplants.